COMPENSATION RELATED TO THE USE OF NUCLEAR ENERGY IN THE HEALTH SECTOR - Yanti Fristikawati; Eddie I. Doloksaribu Doloksaribu; Samuel Hutabarat Hutabarat (Jurnal Paradigma Hukum Pembangunan, 2026)
The use of nuclear medicine has its role to prevent and treat patients from their illness, such as diagnosing cancer, and the treatment of cancer and cardiovascular diseases. They can also help to monitor malnutrition or obesitas on its form. On the other hand, people are still worried about the use of nuclear, they always think about the impact of the Chornobyl accident and using nuclear for weapons. The International Atomic Energy Agency (IAEA) is an International organisation that has the main function to encourage and assist research, development, and practical application of atomic energy for peaceful uses throughout the world. Some regulations in Indonesia and also international conventions already exist to regulate the use of nuclear energy. Indonesia has the Law number 10 of 1997 on Nuclear Energy, and some regulations on the use of nuclear energy in medicine, which also mention compensation. Internationally, the Vienna Convention on Civil Liability for Nuclear Damage and the Convention on Supplementary Compensation for Nuclear Damage (CSC). This article will discuss the compensation for patient that has the damage from the use of nuclear medicine and how it can protect people from the use of nuclear techniques in medicine. From the regulations of conventions and IAEA Standards, the use of nuclear techniques in the medical field is safe for people and the environment as long as they follow the rules.